Effect of Insecurity on Socioeconomic Development in Osun State Nigeria - Mufutau Akanmu Popoola; Shittu Muili Olawale (Journal of Business Management and Economics, 2020)
This study analyzed the effect of insecurity on socioeconomic development in Osun state Nigeria, from 20018 to 2019. Based on the incidents of farmers and herders conflicts with the major interest in the experience in Osun state, Nigeria. Through the application of frustration – aggression theory of John Dollard (1939). The study delved into thorough investigation of the causes, the effects of conflict and to look inward the issue of security standard of the state with the interest of providing information on the outbreak of the conflicts in Osun state. The researcher employed a descriptive method in carrying out the findings, a random sampling through the distribution of questionnaire to 65respondents; the data obtained from survewere analyzed through the uses of Statistical Package for the Social Sciences (SPSS) software. More so, the use of secondary data such as books, relevant articles, news papers and government publications in Nigeria was used, after conducted the data analysis, it was found that the conflicts between farmers and herders are stimulated by multi – causal factors due to limited resources to satisfy greater needs, reprisal attack, and shortage of pasture land couple with climate change among others. From the findings, it was revealed that farmers – herdsmen conflicts poseda disintegrated consequence on the state which affect socioeconomic development in the state. It was also revealed that trans-movement of Fulani pastorialist-herders from far north to the Osun state, Nigeria because of desertification. Therefore, the study recommended that the government at all level should constitute a forum to seeks for previous peaceful coexistence and trace for adoption.